2022
DOI: 10.1111/ene.15380
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic features of Heidenhain variant of Creutzfeldt−Jakob disease: A retrospective case series study

Abstract: Creutzfeldt-Jakob disease (CJD) is an invariably fatal neurodegenerative disease, caused by tissue deposition of a misfolded prion protein (PrP) [1]. It is categorized etiologically into sporadic, genetic, iatrogenic, and variant forms [2]. The genetic form of CJD, accounting for approximately 10%-15% of all cases, results from prion protein encoding gene PRNP mutation and is inherited with an autosomal dominant pattern [2].While CJD classically presents as rapidly progressive dementia, a small subgroup of cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…For all SCAs, significance was calculated in a one-way ANOVA with Bonferroni correction for multiple comparisons to PK1-KD cells reconstituted with moPrP WT . It is indicated by *** for p ≤0.0002, * for p ≤0.005 (Yang et al , 2022). …”
Section: Resultsmentioning
confidence: 99%
“…For all SCAs, significance was calculated in a one-way ANOVA with Bonferroni correction for multiple comparisons to PK1-KD cells reconstituted with moPrP WT . It is indicated by *** for p ≤0.0002, * for p ≤0.005 (Yang et al , 2022). …”
Section: Resultsmentioning
confidence: 99%
“…Thus, this symptom may be overlooked, and a proportion of patients may visit the ophthalmology clinic. A previous study revealed that 35% of HvCJD cases presented to ophthalmologists were misdiagnosed with vitreous opacity, macular degeneration, or cataracts [ 2 ]. This can delay treatment and increase the risk of iatrogenic transmission via surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are a few case reports of HvCJD patients harboring prion protein gene ( PRNP ) mutations, such as E196A, T188K, V180I, and V210I [ 12 , 13 , 14 , 15 ]. A recent study showed that up to 20% of HvCJD cases are genetic [ 2 ]. Compared to sporadic HvCJD, the genetic form of HvCJD is associated with a significantly longer survival duration [ 2 ], but due to the small sample size of genetic HvCJD, a future study will need to be conducted to verify this finding.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations